Mainstreaming gender in climate services: a new tool from CCAFS/IRI - Turner, Jacquelyn (2019)
Access to up to date climate information helps smallholder farmers make informed agriculture decisions. However, due to gender-related factors, women and men can face differing challenges and opportunities to access climate-related information as well as using it to improve management and benefitting from those improved management decisions. To ensure equal distribution of benefits and promote gender equality, it is critical that food security and climate-resiliency initiatives take into account gender considerations from the earliest planning stages. In celebration of World Meteorological Day 2019, learn how CCAFS research uses tools like the CCAFS Gender Checklist to ensure weather information is more accessible to women farmers.